2018
DOI: 10.1111/1467-6427.12226
|View full text |Cite
|
Sign up to set email alerts
|

Family therapy and systemic interventions for child‐focused problems: the current evidence base

Abstract: This review updates previous similar papers published in JFT in 2000, 2009 and 2014. It presents evidence from meta‐analyses, systematic literature reviews, narrative literature reviews and controlled trials for the effectiveness of systemic interventions for families of children and adolescents with common mental health problems and other difficulties. In this context, systemic interventions include both family therapy and other family‐based approaches such as parent training, or parent implemented behavioura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
82
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(108 citation statements)
references
References 243 publications
3
82
0
8
Order By: Relevance
“…The challenge remains though in that individual treatment models presuppose the willingness of a depressed adolescent to recognize problems, engage with services and comply with the treatment, which is often not the case. Thus, researchers are increasingly recommending the development of adolescent depression prevention and early intervention programs that involve creating a supportive family engagement and monitoring (Carr, 2018;Cassels et al, 2018;Dardas, van de Water, & Simmons, 2018;Diamond & Josephson, 2005;Diamond et al, 2010;Ewing, Diamond, & Levy, 2015;Lewis et al, 2013;Poole et al, 2018;Yuen, Fuligni, Gonzales, & Telzer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The challenge remains though in that individual treatment models presuppose the willingness of a depressed adolescent to recognize problems, engage with services and comply with the treatment, which is often not the case. Thus, researchers are increasingly recommending the development of adolescent depression prevention and early intervention programs that involve creating a supportive family engagement and monitoring (Carr, 2018;Cassels et al, 2018;Dardas, van de Water, & Simmons, 2018;Diamond & Josephson, 2005;Diamond et al, 2010;Ewing, Diamond, & Levy, 2015;Lewis et al, 2013;Poole et al, 2018;Yuen, Fuligni, Gonzales, & Telzer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As such, familybased interventions have been promising for advancing both PMH and CMH (Cluxton-Keller, Riley, Noazin, & Umoren, 2015;Galbally & Lewis, 2017;Poole et al, 2018). Using a family systems approach, family interventions can address a range of risk factors that may reciprocally undermine family mental health (Carr, 2018;Kazdin, 2015), such as hostile parenting (e.g., Chang, Schwartz, Dodge, & McBride- Chang, 2003;Edwards & Maguire, 2011) and family conflict (e.g., Herrenkohl, Lee, Kosterman, & Hawkins, 2012;Lewis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Family-based interventions are considered one of the most effective treatments in supporting the reduction of CMH disorders (Carr, 2018). Meta-analytic and systematic reviews have found family and parenting interventions are effective in treating a broad range of emotional (e.g., anxiety disorders; Creswell & Cartwright-Hatton, 2007), behavioural (e.g., delinquency; Maughan, Christiansen, Jenson, Olympia, & Clark, 2005), and substance use problems (United Nations Office on Drugs and Crime [UNODC], 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This paper summarizes the evidence base for systemic therapy with adult‐focused problems, and updates previous reviews (Carr, ). It is also a companion paper to a review of research on the effectiveness of systemic interventions for child‐focused problems (Carr, ). The overall effectiveness of systemic therapy is now well established.…”
Section: Introductionmentioning
confidence: 99%